2017
DOI: 10.5658/wood.2017.45.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Wood Classification in Korean Softwood Species Using Near-infrared Spectroscopy Based on Their Chemical Compositions

Abstract: This study was to establish the interrelation between chemical compositions and near infrared (NIR) spectra for the classification on distinguishability of domestic gymnosperms. Traditional wet chemistry methods and infrared spectral analyses were performed. In chemical compositions of five softwood species including larch (Larix kaempferi), red pine (Pinus densiflora), Korean pine (Pinus koraiensis), cypress (Chamaecyparis obtusa), and cedar (Cryptomeria japonica), their extractives and lignin contents provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 10 publications
2
19
0
2
Order By: Relevance
“…Extractive substances consist of various organic compounds such as triglycerides, fatty acids and sterols (Nascimento et al, 2013) and phenolic compounds such as tannins (Fava et al, 2006), flavonoids (Sirmah et al 2009) with low molecular weight which are found in the lumen and part of the cell wall. The amount and type of plant extractive substances depend on their location (Grabner et al 2005), type of plant, place of growth and climatic conditions (Park et al 2017). Extractive substances that can dissolve in organic solvents such as benzene alcohol solutions include waxes, fats, resins, oils, and tannins as well as certain components that are not soluble in ether (Sjostrom 1998).…”
Section: Extractive Substancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Extractive substances consist of various organic compounds such as triglycerides, fatty acids and sterols (Nascimento et al, 2013) and phenolic compounds such as tannins (Fava et al, 2006), flavonoids (Sirmah et al 2009) with low molecular weight which are found in the lumen and part of the cell wall. The amount and type of plant extractive substances depend on their location (Grabner et al 2005), type of plant, place of growth and climatic conditions (Park et al 2017). Extractive substances that can dissolve in organic solvents such as benzene alcohol solutions include waxes, fats, resins, oils, and tannins as well as certain components that are not soluble in ether (Sjostrom 1998).…”
Section: Extractive Substancesmentioning
confidence: 99%
“…This was because SBW's lignin was higher than SPW (Table 1). Cellulose and hemicellulose were indicated by absorption at wavenumber of 1,400-875 cm -1 , lignin at 1,700-1,200 cm -1 and extractive at 1,700 cm -1 (Park et al 2017). Cellulose is indicated by the high absorption of the-OH and C-O bonds, hemicellulose is indicated by the absorption of compounds with C=O double bonds (Yang et al 2007) while lignin is indicated by the high absorption of single bonds and carbon double bonds.…”
Section: Ftir (Fourier Transform Infrared Spectrophotometer) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, the authors collected realtime information on wood analysis using NIR spectroscopy. In particular, the authors' research group reported the analyses of the physical and chemical properties of Korean coniferous species used as interior and exterior materials in architecture, leading to automatic classification of the species (Kwon et al 2017(Kwon et al , 2019Park et al 2017Park et al , 2018Yang et al 2017Yang et al , 2019aYeon et al 2019;Yang et al 2020). The Korean species used in the study were derived not only from one specific region but also from various latitudinal regions within Korea, and involved Larix kaempferi (Larch), Pinus densiflora (red pine), Pinus koraiensis (Korean pine), Cryptomeria japonica (cedar), and Chamaecyparis obtuse (cypress).…”
Section: Introductionmentioning
confidence: 99%
“…A study on the classification of wood species using NIR spectroscopy has developed a model by performing multivariate linear regression on spectra acquired from powder or a solid lumber surface. 2631 Since wood has different light-scattering properties depending on the direction of incidence due to the anisotropic cell structure, 26,32 it is more accurate to apply the model using a powder sample with higher homogeneity. Nevertheless, to perform a non-destructive measurement, which is a prior advantage of NIR spectroscopy, it is necessary to classify the species as solid lumber.…”
Section: Introductionmentioning
confidence: 99%